Steel with chitin composite zinc-nickel plating coating as well as preparation method and application of steel
By using a steel preparation method of chitin composite galvanized nickel coating on marine engineering equipment, the problem of zinc-nickel alloy electroplating coating being corroded by microorganisms in seawater is solved, and the dual protection against electrochemical and microorganism corrosion is achieved. Extend the service life of the material.
Patent Information
- Application Number
- CN202411300975.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the existing zinc-nickel alloy electroplating coating is soaked in seawater for a long time, it is easily corroded by marine microorganisms, resulting in corrosion of the material matrix and unable to effectively protect against electrochemical and microorganism corrosion.
The preparation method of steel made of chitin composite galvanized nickel coating is activated by irradiating the pretreated steel under ultraviolet lamp and soaking it in hydrochloric acid or oxalic acid, and then containing zinc sulfate heptahydrate, sodium sulfate, boric acid, and 18 hydrate Potential electroplating is performed in the electrolyte of aluminum sulfate, nickel sulfate hexahydrate and chitin to form a uniform chitin composite galvanized nickel coating.
The chitin composite galvanized nickel coating prepared by this method not only has excellent electrochemical protection performance, but also can effectively inhibit microbial adhesion and corrosion and extend the service life of the material.
Smart Images

Figure CN119162632A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antifouling coating materials, and in particular to a steel material with a chitosan composite zinc-nickel coating, and a preparation method and application thereof. Background Art
[0002] In addition to electrochemical corrosion of the material matrix, microorganisms in the environment usually attach to the surface of the material to form a biofilm, which changes the physical and chemical properties of the biofilm and the material surface, leading to local corrosion (pitting). Especially for marine engineering equipment (such as ocean-going ships, warships, and materials immersed in seawater all year round), they are not only corroded by seawater (electrochemical corrosion), but also affected by marine microbial contamination. These marine microorganisms attach to the surface of marine engineering equipment in large numbers, continue to grow and reproduce, and eventually destroy the material itself and even the coating applied on the surface of the material.
[0003] At present, the microbial anti-corrosion measures for marine engineering equipment mainly include sterilization, mechanical removal, addition of bactericides or antibacterial agents, and the use of electrolytic anti-fouling and anti-corrosion devices; among them, the use of electrolytic anti-fouling and anti-corrosion methods is one of the most effective methods. By adding protective coatings such as chrome plating, zinc plating, etc. on the surface of the hull, a protective layer is formed to avoid damage to the material matrix.
[0004] Zinc-nickel alloy electroplating coatings are studied and developed for their excellent corrosion resistance and excellent mechanical properties. The electroplated coating of zinc-nickel alloy electroplating coatings on stainless steel is an anodic coating with good anti-corrosion properties. It can play an effective electrochemical protection role for the material substrate coated with zinc-nickel alloy electroplating coatings and is widely used in automobile manufacturing and national defense. However, zinc-nickel alloy electroplating coatings are immersed in seawater for a long time, and will inevitably be corroded by microorganisms in seawater, causing the coated material substrate to eventually be corroded.
[0005] Therefore, there is an urgent need for a coating that can cover the material matrix and protect against both electrochemical corrosion and microbial corrosion, thereby delaying the corrosion time of the material. Summary of the invention
[0006] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and to provide a steel material with a chitosan composite zinc-nickel coating and a preparation method and application thereof.
[0007] The first object of the present invention is to provide a method for preparing a steel material having a chitosan composite zinc-nickel coating.
[0008] The second object of the present invention is to provide a steel material having a chitosan composite zinc-nickel coating prepared by the above preparation method.
[0009] The third object of the present invention is to provide the use of the above-mentioned steel material with chitosan composite zinc-nickel coating in the manufacture of marine engineering equipment.
[0010] In order to achieve the above object, the present invention is implemented by the following scheme:
[0011] A method for preparing a steel material having a chitosan composite zinc-nickel coating comprises the following steps:
[0012] S1. The pretreated steel is placed under ultraviolet light, and then immersed in hydrochloric acid and / or oxalic acid for 4 to 30 seconds to obtain an activated steel; the pretreatment is degreasing and / or rust removal;
[0013] S2. The activated steel obtained in step S1 and the electrolyte are electroplated using a constant potential to obtain a steel having a chitosan composite zinc-nickel coating;
[0014] The electrolyte contains 200-300 g / L of zinc sulfate heptahydrate, 70-90 g / L of sodium sulfate, 20-30 g / L of boric acid, 35-45 g / L of aluminum sulfate 18hydrate, 20-40 g / L of nickel sulfate hexahydrate, 0.2-1 g / L of chitin and / or 10-20 g / L of a complexing agent; the complexing agent is ethylenediaminetetraacetic acid, hydroxyethylidene diphosphonic acid or aminotrimethylphosphonic acid;
[0015] The entire constant potential electroplating process is carried out in a microwave environment with a microwave power of 300 to 600W.
[0016] Preferably, the steel material in step S1 is carbon structural steel, low alloy high strength structural steel and / or low carbon steel.
[0017] More preferably, the steel is Q235B steel, Q355 steel and / or 20# carbon steel.
[0018] Preferably, the concentration of the hydrochloric acid and / or oxalic acid in step S1 is 0.5-1.5 mol / L.
[0019] More preferably, the concentration of the hydrochloric acid and / or oxalic acid is 1 mol / L.
[0020] Preferably, the degreasing in step S1 is specifically: immersing the steel in acetone for 10 to 30 minutes and then immersing it in anhydrous ethanol for 10 to 30 minutes.
[0021] More preferably, the steel material is immersed in acetone for 10 minutes and then immersed in anhydrous ethanol for 10 minutes.
[0022] Preferably, the rust removal in step S1 is pickling rust removal.
[0023] More preferably, the rust removal is rust removal by washing with hydrochloric acid.
[0024] Preferably, the electrolyte in step S2 contains 200-300 g / L of zinc sulfate heptahydrate, 70-90 g / L of sodium sulfate, 20-30 g / L of boric acid, 35-45 g / L of aluminum sulfate 18hydrate, 20-40 g / L of nickel sulfate hexahydrate, 0.2 g / L of chitosan and / or 10-20 g / L of a complexing agent.
[0025] More preferably, the electrolyte contains 250 g / L zinc sulfate heptahydrate, 80 g / L sodium sulfate, 26 g / L boric acid, 40 g / L aluminum sulfate 18hydrate, 30 g / L nickel sulfate hexahydrate, 0.2 g / L chitosan and / or 15 g / L complexing agent.
[0026] Preferably, during the constant potential electroplating in step S2, the deposition current density is 10-30 mA / cm 2 The electroplating time is 10 to 60 minutes.
[0027] More preferably, the deposition current density is 20 mA / cm 2 , the electroplating time is 30min.
[0028] More preferably, during the constant potential electroplating in step S2, the activated steel obtained in step S1 is used as the working electrode, the zinc electrode is used as the counter electrode, and the calomel is used as the reference electrode.
[0029] The present invention also seeks to protect the steel material having a chitosan composite zinc-nickel coating prepared by any of the above-mentioned preparation methods.
[0030] The present invention also seeks to protect the use of the steel material having the chitin composite zinc-nickel coating in the manufacture of marine engineering equipment.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention provides a method for preparing a steel material with a chitosan composite zinc-nickel coating, wherein the method comprises the steps of subjecting an activated steel material to constant potential electroplating with an electrolyte to obtain a steel material with a chitosan composite zinc-nickel coating; the electrolyte is obtained by uniformly mixing a plating solution and a complexing agent, and the plating solution contains 200 to 300 g / L of zinc sulfate heptahydrate, 70 to 90 g / L of sodium sulfate, 20 to 30 g / L of boric acid, 35 to 45 g / L of aluminum sulfate 18hydrate, 20 to 40 g / L of nickel sulfate hexahydrate, and 0.2 to 1 g / L of chitosan. The steel material with a chitosan composite zinc-nickel coating prepared by the preparation method not only has good uniformity of the electroplating coating, but also has an inhibitory effect, can resist microbial fouling, and has excellent corrosion resistance. When used as a manufacturing material for marine engineering equipment, it can effectively avoid the attachment of marine microorganisms, reduce microbial fouling, and thus increase its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is the XRD spectrum of the steel with chitin composite zinc-nickel coating in Test Example 1;
[0034] Figure 2 is a polarization curve diagram of the steel with chitosan composite zinc-nickel coating in Test Example 1;
[0035] Figure 3 This is a graph showing the antibacterial test results of the Q355 steel material 2 having a chitin composite zinc-nickel coating in Test Example 1;
[0036] Figure 4 This is a graph showing the antibacterial test results of the 20# carbon steel material 3 having a chitin composite zinc-nickel coating in Test Example 1. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with the accompanying drawings and specific examples of the specification. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0038] Example 1 A Q235B steel material with a chitin composite zinc-nickel coating
[0039] A Q235B steel material with a chitosan composite zinc-nickel coating, the preparation method comprising the following steps:
[0040] S1. The Q235B steel sheet was immersed in acetone, ultrasonically cleaned in an ultrasonic cleaning machine for 10 min, then the Q235B steel sheet was taken out and immersed in anhydrous ethanol for 10 min, then the steel sheet was taken out and rinsed with deionized water for 2 min to obtain a degreased Q235B steel sheet;
[0041] The degreased Q235B steel sheet was immersed in 1 mol / L hydrochloric acid to remove rust, then immersed in anhydrous ethanol for 10 min of ultrasonic treatment, taken out and blown dry with nitrogen (N2) to obtain a pretreated Q235B steel sheet.
[0042] The pretreated Q235B steel sheet was irradiated under a 254nm ultraviolet lamp for 30 minutes, and then immersed in 1mol / L hydrochloric acid (HCl) for 5 seconds. After the immersion, it was dried with nitrogen to obtain an activated Q235B steel sheet.
[0043] S2. Add 37.5g of zinc sulfate heptahydrate (ZnSO4·7H2O), 12g of sodium sulfate (Na2SO4), 3.9g of boric acid (H3BO3), 6g of aluminum sulfate 18hydrate {Al2(SO4)3·18H2O} and 4.5g of nickel sulfate hexahydrate (NiSO4·6H2O) to 150mL of deionized water, stir thoroughly until clear, then add 0.03g of chitosan, stir for 10min (evenly dispersed), then add ethylenediaminetetraacetic acid to a final concentration of 15g / L, stir for 30min to obtain electrolyte 1; the concentration of chitosan in electrolyte 1 is 0.2g / L.
[0044] S3. Add the electrolyte 1 obtained in step S2 to the electroplating tank, set the zinc electrode in the electroplating process as the counter electrode, the activated Q235B steel sheet obtained in step S1 as the working electrode, and the calomel as the reference electrode. The deposition current density is 20 mA / cm 2 The electroplating tank was placed in a microwave environment with a microwave power of 400 W, and constant potential electroplating was used for 30 minutes. After the electroplating was completed, the Q235B steel sheet was taken out and rinsed with deionized water for 10 seconds, dried with nitrogen, and placed in an oven at 60°C to obtain Q235B steel 1 with a chitosan composite zinc-nickel coating.
[0045] Example 2 A Q355 steel material with a chitosan composite zinc-nickel coating
[0046] A Q355 steel material with a chitosan composite zinc-nickel coating, the preparation method comprising the following steps:
[0047] S1. The Q355 steel sheet was immersed in acetone, ultrasonically cleaned in an ultrasonic cleaning machine for 10 min, then the Q355 steel sheet was taken out and immersed in anhydrous ethanol for 10 min, then the steel sheet was taken out and rinsed with deionized water for 2 min to obtain the degreased Q355 steel sheet;
[0048] The degreased Q355 steel sheet was immersed in 1 mol / L hydrochloric acid to remove rust, then immersed in anhydrous ethanol for 10 min of ultrasound, taken out and blown dry with nitrogen (N2) to obtain a pretreated Q355 steel sheet.
[0049] The pretreated Q355 steel sheet was irradiated under a 254 nm ultraviolet lamp for 30 min, and then immersed in 1 mol / L hydrochloric acid (HCl) for 6 s. After the immersion, it was dried with nitrogen to obtain an activated Q355 steel sheet.
[0050] S2. Add 37.5g of zinc sulfate heptahydrate (ZnSO4·7H2O), 12g of sodium sulfate (Na2SO4), 3.9g of boric acid (H3BO3), 6g of aluminum sulfate 18hydrate {Al2(SO4)3·18H2O} and 4.5g of nickel sulfate hexahydrate (NiSO4·6H2O) to 150mL of deionized water, stir thoroughly until clear, then add 0.09g of chitosan, stir for 10min (evenly dispersed), then add hydroxyethylidene diphosphonic acid to a final concentration of 10g / L, stir for 30min to obtain electrolyte 2; the concentration of chitosan in electrolyte 2 is 0.6g / L.
[0051] S3. Add the electrolyte 2 obtained in step S2 to the electroplating tank, set the zinc electrode in the electroplating process as the counter electrode, the activated Q355 steel sheet obtained in step S1 as the working electrode, and the calomel as the reference electrode. The deposition current density is 20 mA / cm 2 The electroplating tank was placed in a microwave environment with a microwave power of 400 W, and constant potential electroplating was used for 40 minutes. After the electroplating was completed, the Q355 steel sheet was taken out and rinsed with deionized water for 10 seconds, dried with nitrogen, and placed in an oven at 60°C to obtain Q355 steel 2 with a chitosan composite zinc-nickel coating.
[0052] Example 3 A 20# carbon steel material with a chitosan composite zinc-nickel coating
[0053] A 20# carbon steel material with a chitosan composite zinc-nickel coating, the preparation method comprising the following steps:
[0054] S1. The 20# carbon steel sheet was immersed in acetone, ultrasonicated in an ultrasonic cleaning machine for 10 minutes, then the 20# carbon steel sheet was taken out and immersed in anhydrous ethanol for 10 minutes, then the steel sheet was taken out and rinsed with deionized water for 2 minutes to obtain the degreased 20# carbon steel sheet;
[0055] The degreased 20# carbon steel sheet was immersed in 1 mol / L hydrochloric acid to remove rust, then immersed in anhydrous ethanol for 10 minutes of ultrasound, taken out and blown dry with nitrogen (N2) to obtain a pretreated 20# carbon steel sheet.
[0056] The pretreated 20# carbon steel sheet was irradiated under a 254nm ultraviolet lamp for 30 minutes, and then immersed in 1mol / L hydrochloric acid (HCl) for 8 seconds. After the immersion, it was dried with nitrogen to obtain an activated 20# carbon steel sheet.
[0057] S2. Add 37.5g of zinc sulfate heptahydrate (ZnSO4·7H2O), 12g of sodium sulfate (Na2SO4), 3.9g of boric acid (H3BO3), 6g of aluminum sulfate 18hydrate {Al2(SO4)3·18H2O} and 4.5g of nickel sulfate hexahydrate (NiSO4·6H2O) to 150mL of deionized water, stir thoroughly until clear, then add 0.15g of chitosan, stir for 10min (evenly dispersed), then add aminotri(methylenephosphoric acid) to a final concentration of 20g / L, stir for 30min to obtain electrolyte 3; the concentration of chitosan in electrolyte 3 is 1.0g / L.
[0058] S3. Add the electrolyte 3 obtained in step S2 to the electroplating tank, set the zinc electrode in the electroplating process as the counter electrode, the activated 20# carbon steel sheet obtained in step S1 as the working electrode, and the calomel as the reference electrode. The deposition current density is 20 mA / cm 2 The electroplating tank was placed in a microwave environment with a microwave power of 500 W, and constant potential electroplating was used for 30 minutes. After the electroplating was completed, the 20# carbon steel sheet was taken out and rinsed with deionized water for 10 seconds, dried with nitrogen, and placed in an oven at 60°C to obtain 20# carbon steel material 3 with a chitosan composite zinc-nickel coating.
[0059] Comparative Example 1 A Q235B steel material with a composite zinc-nickel coating
[0060] The only difference between the preparation method of a Q235B steel with a composite zinc-nickel coating and the preparation method shown in Example 1 is that no chitosan is added to the electrolyte shown in step S2, and the remaining treatments are exactly the same to prepare a Q235B steel with a composite zinc-nickel coating.
[0061] Test Example 1 Performance test of steel with chitin composite zinc-nickel coating
[0062] 1. Experimental Methods
[0063] 1.XRD test
[0064] The Q235B steel material 1 (chitosan concentration 0.2 g / L) with a chitosan composite zinc-nickel coating prepared in Example 1, the Q355 steel material 2 (chitosan concentration 0.6 g / L) with a chitosan composite zinc-nickel coating prepared in Example 2, and the 20# carbon steel material 3 (chitosan concentration 1.0 g / L) with a chitosan composite zinc-nickel coating prepared in Example 3 were respectively analyzed by powder diffraction to obtain XRD diffraction patterns;
[0065] When the powder diffraction method is used for phase analysis, the parameters are set as follows: tube voltage 40 kV, tube current 40 mA, test range 10-80°, step length 0.02°, and scanning speed 4° / min.
[0066] 2. Polarization curve test
[0067] A platinum electrode was used as the counter electrode, and a saturated calomel electrode connected by a salt bridge of a saturated potassium nitrate solution was used as the reference electrode. The test frequency range was set to 0.01 Hz to 100 kHz, and the scanning potential was -1.55 to -1 V.
[0068] The Q235B steel 1 with a chitosan composite zinc-nickel coating prepared in Example 1 (chitosan concentration: 0.2 g / L), the Q355 steel 2 with a chitosan composite zinc-nickel coating prepared in Example 2 (chitosan concentration: 0.6 g / L), and the Q235B steel with a composite zinc-nickel coating prepared in Comparative Example 1 (chitosan concentration: 0 g / L) were used as working electrodes to form an electrode system for testing electrochemical impedance spectroscopy.
[0069] The polarization curve is plotted with the self-corrosion potential as the horizontal axis and the self-corrosion current density as the vertical axis.
[0070] 3. Antibacterial test
[0071] Staphylococcus aureus was inoculated in a culture dish and incubated at 37°C for 12 h. Then, the Q355 steel 2 (chitin concentration: 0.6 g / L) with a chitosan composite zinc-nickel coating prepared in Example 2 with a diameter of 15 mm was placed in the center of the culture dish inoculated with Staphylococcus aureus in a sterile environment. After irradiation under simulated sunlight for 24 h, photos were taken and the size of the inhibition zone was measured.
[0072] According to the above method, the 20# carbon steel material 3 (chitosan concentration 1.0 g / L) with chitosan composite zinc-nickel coating prepared in Example 3 was subjected to an antibacterial test, and the size of the antibacterial zone was measured.
[0073] 2. Experimental Results
[0074] 1. XRD spectrum test results
[0075] The XRD pattern of steel with chitin composite zinc-nickel coating is as follows Figure 1 As shown, the results show that in the XRD spectrum, the three steels with chitosan composite zinc-nickel coatings prepared in Examples 1 to 3 all have sharper diffraction peaks at 43.19° and 44.63°, which are consistent with the diffraction peaks of hexagonal close-packed lattice Zn (standard card JCPDS No.65-5973).
[0076] It is explained that the main phase of the coating on the three kinds of steel materials with chitosan-zinc-nickel coating prepared in Examples 1 to 3 is Zn coating and has excellent crystallinity.
[0077] 2. Polarization curve test results
[0078] The polarization curve of steel with chitin composite zinc-nickel coating is as follows Figure 2 The polarization curve fitting results are shown in Table 1.
[0079] Table 1 Polarization curve fitting results
[0080] Comparative Example 1 Example 1 Example 2 Concentration of added chitosan 0g / L 0.2g / L 0.6g / L Ecorr / V -1.3910 -1.3739 -1.3720 <![CDATA[I corr / μA·cm -2 ]]> 393.4 168.7 181.0
[0081] The results show that the self-corrosion potential of the Q235B steel (pure zinc-nickel coated steel) prepared in Comparative Example 1 is -1.3910 V, and the self-corrosion current density is 393.4 μA·cm -2 The self-corrosion potentials of the Q235B steel 1 (chitosan concentration 0.2 g / L) with a chitosan composite zinc-nickel coating prepared in Example 1 and the Q355 steel 2 (chitosan concentration 0.6 g / L) with a chitosan composite zinc-nickel coating prepared in Example 2 are both around -1.37 V, while the self-corrosion current density of the Q235B steel 1 (chitosan concentration 0.2 g / L) with a chitosan composite zinc-nickel coating is the smallest, which is only 168.7 μA·cm -2 The self-corrosion current density of Q355 steel 2 (chitosan concentration 0.6 g / L) with chitosan composite zinc-nickel coating is 181.0 μA·cm -2 .
[0082] The results show that the corrosion resistance of the Q235B steel 1 (chitosan concentration 0.2 g / L) with a chitosan composite zinc-nickel coating prepared in Example 1 and the Q355 steel 2 (chitosan concentration 0.6 g / L) with a chitosan composite zinc-nickel coating prepared in Example 2 are significantly better than that of the Q23B steel with a composite zinc-nickel coating prepared in Comparative Example 1; and the self-corrosion current density of the Q235B steel 1 (chitosan concentration 0.2 g / L) with a chitosan composite zinc-nickel coating prepared in Example 1 is significantly lower than that of other steels, indicating that its corrosion resistance is the best.
[0083] 3. Antibacterial test results
[0084] The antibacterial test results of Q355 steel 2 (chitosan concentration 0.6g / L) with chitosan composite zinc-nickel coating are shown in the figure below: Figure 3 As shown in the figure, the antibacterial test results of 20# carbon steel 3 (chitosan concentration 1.0g / L) with chitosan composite zinc-nickel coating are as follows Figure 4 shown.
[0085] The results showed that the Q355 steel 2 with chitosan composite zinc-nickel coating (chitosan concentration 0.6 g / L) and the 20# carbon steel 3 with chitosan composite zinc-nickel coating (chitosan concentration 1.0 g / L) showed significant inhibitory effects on the growth of Staphylococcus aureus. Figure 3 The diameter of the inhibition zone is 18 mm. Figure 4 The diameter of the inhibition zone in the test tube is 25 mm.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. For ordinary technicians in this field, other different forms of changes or modifications can be made based on the above descriptions and ideas. It is not necessary and impossible to list all the implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a steel material having a chitosan composite zinc-nickel coating, It is characterized in that The following steps are involved: S1. The pretreated steel is placed under ultraviolet light, and then immersed in hydrochloric acid and / or oxalic acid for 4 to 30 seconds to obtain an activated steel; the pretreatment is degreasing and rust removal; S2. The activated steel obtained in step S1 and the electrolyte are electroplated using a constant potential to obtain a steel having a chitosan composite zinc-nickel coating; The electrolyte contains 200-300 g / L of zinc sulfate heptahydrate, 70-90 g / L of sodium sulfate, 20-30 g / L of boric acid, 35-45 g / L of aluminum sulfate 18hydrate, 20-40 g / L of nickel sulfate hexahydrate, 0.2-1 g / L of chitin and / or 10-20 g / L of a complexing agent; the complexing agent is ethylenediaminetetraacetic acid, hydroxyethylidene diphosphoric acid or aminotrimethylphosphoric acid; wherein the constant potential electroplating is carried out in a microwave environment with a microwave power of 300-600 W.
2. The preparation method according to claim 1, It is characterized in that The steel material in step S1 is carbon structural steel, low alloy high strength structural steel and / or low carbon steel.
3. The preparation method according to claim 1, It is characterized in that The concentration of the hydrochloric acid and / or oxalic acid in step S1 is 0.5-1.5 mol / L.
4. The preparation method according to claim 1, It is characterized in that The degreasing in step S1 is specifically as follows: immersing the steel in acetone for 10 to 30 minutes and then immersing the steel in anhydrous ethanol for 10 to 30 minutes.
5. The preparation method according to claim 1, It is characterized in that The electrolyte in step S2 contains 200-300 g / L of zinc sulfate heptahydrate, 70-90 g / L of sodium sulfate, 20-30 g / L of boric acid, 35-45 g / L of aluminum sulfate 18hydrate, 20-40 g / L of nickel sulfate hexahydrate, 0.2 g / L of chitin and / or 10-20 g / L of a complexing agent.
6. The preparation method according to claim 5, It is characterized in that The electrolyte contains 250 g / L of zinc sulfate heptahydrate, 80 g / L of sodium sulfate, 26 g / L of boric acid, 40 g / L of aluminum sulfate 18hydrate, 30 g / L of nickel sulfate hexahydrate, 0.2 g / L of chitin and / or 15 g / L of a complexing agent.
7. The preparation method according to claim 1, It is characterized in that During the constant potential electroplating in step S2, the deposition current density is 10-30 mA / cm 2 The electroplating time is 10 to 60 minutes.
8. The preparation method according to claim 7, It is characterized in that The deposition current density was 20 mA / cm 2 , the electroplating time is 30min.
9. Steel material with chitosan composite zinc-nickel coating prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the steel material with chitosan composite zinc-nickel coating according to claim 9 in the manufacture of marine engineering equipment and / or.
